PRDX2 in Myocyte Hypertrophy and Survival is Mediated by TLR4 in Acute Infarcted Myocardium - Xian Jin (Nature Portfolio, 2017)
Abstract Peroxiredoxin 2 (PRDX2) is an antioxidant and molecular chaperone that can be secreted from tumor cells. But the role of PRDX2 in acute myocardial infarction (AMI) is not clear. In the current study, we demonstrate the role of PRDX2 from clinical trials, H9c2 cells and in a mouse model. ELISA analysis shows that serum concentrations of VEGF and inflammatory factor IL-1β, TNF-α and IL-6 were increased in AMI patients compared to a control group. The expression of PRDX2 was also upregulated. In vivo experiments show that the expression of PRDX2 inhibits hypoxia-induced oxidative stress injury to H9c2 cells. However, PRDX2 expression promotes TLR4 mediated inflammatory factor expression and VEGF expression under hypoxia conditions. PRDX2 overexpression in H9c2 cells also promotes human endothelial cell migration, vasculogenic mimicry formation and myocardial hypertrophy related protein expression. The overexpression of PRDX2 inhibits ROS level and myocardial injury after AMI but promotes inflammatory responses in vivo. Immunocytochemistry and immunofluorescence analysis show that overexpression of PRDX2 promotes angiogenesis and myocardial hypertrophy. Taken together, our results indicate that PRDX2 plays two roles in acute infarction – the promotion of cell survival and inflammatory myocardial hypertrophy.